Combinatorial optimization second international symposium, ISCO 2012, Athens, Greece, April 19-21, 2012, revised selected papers - Mahjoub, A. Ridha (Lecture Notes in Computer Science, 2012)
This book constitutes the thoroughly refereed post-conference proceedings of the Second International Symposium on Combinatorial Optimization, ISCO 2012, held in Athens, Greece, in April 2012. The 37 revised full papers presented together with 4 invited talks were carefully reviewed and selected from 94 regular and 30 short submissions. They present original research on all aspects of combinatorial optimization, ranging from mathematical foundations and theory of algorithms to computational studies and practical applications.